Iatrogenic cerebral amyloid angiopathy and Alzheimer's disease co‐pathology - Francisco Hernández‐Fernández; Isabel Martínez‐Fernández; Rosa Barbella‐Aponte; Inmaculada Feria Vilar; Oscar Ayo‐Martín; Jorge García‐García; Rosa Collado; Alberto Andrés; Mar Hernández‐Guillamón; Francisco José Pena Pardo; Cristina Barrena; Miguel de laFuente; et al. (Annals of Clinical and Translational Neurology)
Abstract Iatrogenic cerebral amyloid angiopathy, a disease caused by contact with neurosurgical material or human growth hormone contaminated by beta‐amyloid peptide (Aβ), has a prion‐like transmission mechanism. We present a series of three patients under 55 years of age who underwent cranial surgery. All of them developed multiple cerebral hemorrhages, transient focal neurological deficits, and/or cognitive impairment after 3–4 decades. MRI was compatible with CAA, and Aβ deposition was confirmed. The third patient, who had a ventriculoperitoneal valve, also showed Aβ deposition in the peritoneum and diagnostic biomarkers of Alzheimer's disease. Co‐pathology with Alzheimer disease and its iatrogenic transmission should be considered.